The Amanaska: king of all yogas. A critical edition and annotated translation with a monographic introduction - Birch, JEG (2013)
This thesis contains a critical edition, translation and study of the Amanaska, which is a medieval Sanskrit yoga text of one hundred and ninety-eight verses in two chapters (adhyāya). Seventy-five manuscripts have been consulted for this edition and thirty-two were selected for the full collation on the basis of stemmatic analysis on a sample collation of all the manuscripts. The critical apparatus contains references to parallel verses in other works and the notes to the translation provide further information on the content, terminology and obscure passages of the text by citing other Sanskrit works, in particular, earlier Tantras and medieval yoga texts, as well as a Nepalese commentary on the Amanaska. The first part of the Introduction contains a summary of the text and an examination of the colophons of all the available manuscripts in order to establish the proper titles of the text and each of the chapters. Unlike previous editors, I have adopted the title Amanaska because it is found in the great majority of manuscript colophons. The title of previous printed editions, Amanaskayoga, appears to derive from nineteenth-century manuscript catalogues. The authorship of the text has been discussed in light of the claim made in recent Indian scholarship that it was written by Gorakṣanātha, the pupil of Matysendranātha. I conclude that the author is unknown. Discrepancies between the chapters, in particular, various incongruities in content and differences in the limits of dating, strongly suggest that both chapters were originally composed as separate works. Unlike previous editions, this one is based on the north-Indian recension. There is evidence that the north-Indian recension has preserved a more coherent version of the first chapter. The additional verses of the south-Indian recension have been edited and included separately in appendix A. The first part of the Introduction also includes fourteen sections on the content of the Amanaska. The first six of these sections are on absorption (laya), the practice of eliminating reality levels (tattva) and Layayoga, and the following sections cover yogic powers (siddhi), Śāmbhavī Mudrā, the term amanaska and the Amanaska's known sources for verses on the no-mind state. The final section called, 'Amanaska: the Effortless Leap to Liberation' examines the salient teachings of the Amanaska in light of previous ascetic, yogic and tantric traditions, in an attempt to answer questions about whom its intended audience may have been and its place within India's history of yoga. The first part of the Introduction concludes with a discussion of yoga texts which have been either directly or indirectly influenced by the Amanaska. Seeing that many of these texts have not been critically edited or translated, I have discussed their date of composition and their content in addition to the material that derives from the Amanaska. The second part of the Introduction provides essential details on the seventy-four manuscripts consulted for this edition, brief comments on the shortcomings of the previous printed editions and an explanation of the editing methodology. The recensions of the text are discussed in this section as well as my editorial policy. The critical edition and translation of the Amanaska are presented together. Each Sanskrit verse is followed by the translation and its critical apparatus is at the bottom of the page. The endnotes to each verse are located at the end of its respective chapter. Appendices B-E include four stemmatic diagrams along with brief descriptions of each hyparchetype, a list of symbols and abbreviations and an outline of the conventions used in the critical apparatus.